Cardiorespiratory fitness is associated with hippocampal resting state connectivity in women newly diagnosed with breast cancer - Lesnovskaya, Alina; Ripperger, Hayley S.; Donofry, Shannon D.; Drake, Jermon A.; Wan, Lu; Poniatowski, Alexa; Donahue, Patrick T.; Crisafio, Mary E.; Gilmore, Alysha D.; Richards, Emily A.; Grove, George; Gentry, Amanda L.; et al. (Frontiers in Cognition, 2023)
Background: Breast cancer and its treatment are associated with aberrant patterns of resting state functional connectivity (rsFC) between the hippocampus and several areas of the brain, which may account for poorer cognitive outcomes in patients. Higher cardiorespiratory fitness (CRF) has been associated with enhanced rsFC and cognitive performance; however, these associations have not been well studied in breast cancer. We examined the relationship between CRF, rsFC of the hippocampus, and cognitive performance among women newly diagnosed with breast cancer.: Thirty-four postmenopausal women newly diagnosed with Stage 0-IIIa breast cancer (Mage=63.59±5.73) were enrolled in a 6-month randomized controlled trial of aerobic exercise vs. usual care. During baseline assessments, participants completed functional brain imaging, a submaximal CRF test, and cognitive testing. Whole-brain, seed-based analyses were used to examine the relationship between CRF and hippocampal rsFC, with age, years of education, and framewise displacement included as covariates. Cognition was measured with a battery of validated neurocognitive measures, reduced to 7 composite factors.Results: Higher CRF was positively associated with greater rsFC of the hippocampus to a cluster within the dorsomedial and dorsolateral frontal cortex (z-max = 4.37, p = 0.003, cluster extent = 1020 voxels). Connectivity within cluster peaks was not significantly related to cognitive factors (all ps > .05).Discussion: CRF was positively associated with hippocampal rsFC to frontal cortex structures, comprising a network of regions commonly suppressed in breast cancer. Future longitudinal research is needed to explore whether baseline rsFC predicts long-term cognitive resilience in breast cancer.